PESTLE – ANALYSIS AS A TOOL FOR THE DEVELOPMENT AND IMPLEMENTATION OF INNOVATIVE MARKETING IN AN INDUSTRIAL ENTERPRISE - PETROVSKA, Svitlana; YAKIVCHENKO, Andriі (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the diagnosis of the problems of the formation of the management mechanism of innovative marketing of industrial enterprises of Ukraine. The study covers issues of development and limitations in market relations, and also offers a comprehensive approach to the analysis of this topic. The methodological approach to diagnosis includes different levels of analysis – from internal organizational processes to market and social factors. The article presents the algorithm developed by the authors for diagnosing problems and developing a management mechanism for innovative marketing of industrial enterprises. For an in-depth analysis of innovative marketing implementation strategies, the authors of the article have improved the PESTLE analysis method, which allows assessing the influence of political, economic, social, technological, legal and environmental factors. The authors proposed the components for the formation of the PESTLE matrix. The final stage involves evaluating the effectiveness of innovative marketing using appropriate criteria and indicators. The article presents the approbation of the PESTLE analysis technique on the example of an industrial enterprise. An expert assessment was carried out and the main influencing factors and their strength were determined. The results of the study contribute to the identification of problems and the identification of new opportunities for improving the management mechanism of innovative marketing. The article also considers the PESTLE analysis of innovative marketing and emphasizes its importance for the adaptation of enterprises to external changes. The purpose of the article is to diagnose the problems of the formation and development of the innovative marketing management mechanism of industrial enterprises of Ukraine, to determine the main internal and external factors that affect the implementation of innovative solutions, as well as to develop a comprehensive approach to evaluating the effectiveness of innovative marketing using the PESTLE analysis method. In modern conditions, industrial enterprises face numerous challenges related to the dynamic development of the market, changes in the political, economic, social and technological environment. Insufficient understanding of these influencing factors and the lack of a systematic approach to the implementation of innovative marketing can lead to a loss of competitiveness. Therefore, it is necessary to develop a methodological approach to diagnosing problems and determining directions for the development of innovative marketing, taking into account the internal processes of enterprises and external market factors. This is what made it necessary to improve the diagnosis of the management mechanism of innovative marketing at industrial enterprises.
Keywords: innovative marketing; marketing research; mechanism; sustainable development; management; industrial enterprises; PESTLE; innovative approaches